2019
DOI: 10.3389/fneur.2019.00450
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal MRI Brain Scans Reveal Accelerated Brain Aging in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory disorder of the central nervous system. By combining longitudinal MRI-based brain morphometry and brain age estimation using machine learning, we tested the hypothesis that MS patients have higher brain age relative to chronological age than healthy controls (HC) and that longitudinal rate of brain aging in MS patients is associated with clinical course and severity. Seventy-six MS patients [71% females, mean age 34.8 years (range 21–49) at inclusion] were examined wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 37 publications
6
63
0
Order By: Relevance
“…The difference between an individual's chronological age and the age predicted by machine-learning analysis of voxelwise neuroimaging data, the brain-predicted age difference (brain-PAD), has been proposed as an age-adjusted index of structural brain health. Research has shown brain-PAD to be sensitive to neurological and psychiatric diseases, 15,16 including MS. 17,18 Specifically, MS was associated with between 4 and 6 years of added brain-PAD, similar in magnitude to previous work on traumatic brain injury 19 and epilepsy 20 and greater than well-treated HIV 21 or Down's syndrome. 22 Kaufmann and colleagues reported that brain-age gap (equivalent to brain-PAD) was associated with Expanded Disability Status Scale (EDSS) score.…”
supporting
confidence: 78%
“…The difference between an individual's chronological age and the age predicted by machine-learning analysis of voxelwise neuroimaging data, the brain-predicted age difference (brain-PAD), has been proposed as an age-adjusted index of structural brain health. Research has shown brain-PAD to be sensitive to neurological and psychiatric diseases, 15,16 including MS. 17,18 Specifically, MS was associated with between 4 and 6 years of added brain-PAD, similar in magnitude to previous work on traumatic brain injury 19 and epilepsy 20 and greater than well-treated HIV 21 or Down's syndrome. 22 Kaufmann and colleagues reported that brain-age gap (equivalent to brain-PAD) was associated with Expanded Disability Status Scale (EDSS) score.…”
supporting
confidence: 78%
“…In line with a recent implementation in patients with MS (Høgestøl et al 2019a), our results demonstrated high reliability across all timepoints for the global and regional models with ICC ranging from .70 to .86 for the right occipital and the right parietal models respectively. The brain age estimation based on the median of the 12 regional model was amongst the most reliable models with an ICC of .89. across the two baselines and .83 across all timepoints, outperforming the estimation based on all T1 features.…”
Section: Discussionsupporting
confidence: 89%
“…Briefly, combining a wide array of informative brain imaging features in a prediction model allows for an accurate prediction of the age of an unseen individual (Franke et al 2012;Franke et al 2010). The degree to which the model under-or over-estimate the individual's age has been shown to be sensitive to a variety of health-related characteristics, including cognitive function and mortality (Boyle et al 2019;Cole & Franke 2017;Cole et al 2018;Richard et al 2018), and brain age prediction using MRI data has recently been shown to be sensitive both to the clinical manifestation and polygenic risk of various brain disorders (Høgestøl et al 2019a;Kaufmann et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Individual variation in delta estimations are associated with a range of cognitive and biological measures [10,11,12,13,14,15,16,17], including cardiovascular health [14], and differences in brain age have been established between patient groups and healthy controls: individuals with conditions such as Alzheimer's disease, multiple sclerosis, epilepsy, and psychiatric disorders show on average older brain age relative to their chronological age [9,18,19,20,21,22]. Longitudinal studies have documented highly reliable brain age prediction in stroke patients [23], and accelerated brain aging in patients with schizophrenia and multiple sclerosis [21,24,25].…”
Section: Introductionmentioning
confidence: 99%